Practicality Test of the HOTS-Oriented Module on Biology Material for the Second Semester of Grade X in Senior High School/Madrasah Aliyah - Arif, Armin; Hala, Yusminah; Adnan, Adnan (Bioeduca : Journal of Biology Education, 2024)
This study is research and development. This study aims to obtain a practical HOTS-oriented module based on the implementation of the module and the response of teachers and students as practitioners. The research instruments used were module implementation observation sheets, teacher response questionnaires, and student response questionnaires. Practical data collection is carried out by providing implementation observation sheets to observers and response questionnaires are given to teachers and students. The results showed that the implementation of the module had an average score of 4.59 with the category carried out very well, the results of the teacher response questionnaire analysis had an average value of 4.58 with the practical category, and the results of the student response questionnaire analysis had an average value of 4.54 with the practical category. The conclusion of this study is that the HOTS-oriented module on biology material in the even semester of class X high school / MA developed has met the implementation criteria with the category of very well implemented and the response of teachers and students shows that the developed module is practically used in learning.